Full-Time Schools and Educational Trajectories: Evidence from High-Stakes Exams - Francisco Cabrera-Hernández; María Padilla-Romo; Cecilia Peluffo (Institute of Labor Economics (IZA), 2022)
This paper estimates the effects of extending the school day during elementary school on students' education outcomes later in life. We do so in the context of Mexico City's metropolitan area, where a large-scale program introduced in 2007 extended the school day from 4.5 to 8 hours in schools that adopted the program. We exploit cohort-by-cohort variation in students' full-time school enrollment during elementary school to identify the longer-term effects on their performance in a high-school admission exam, subsequent placement, and preferences over high schools. The results indicate that full-time schools have positive and long-lasting effects on students' performance, increasing high-stakes test scores by 4.9 percent of a standard deviation. Exposure to full-time schooling also increases students' probability of choosing highly-selective high schools as their top choices, especially among students from low-SES schools.
Keywords: I21; I25; J01; 330; full-time schools; high-stakes exams; education; Mexico